Quantification and visualization of flood-induced morphological changes in meander structures by UAV-based monitoring - Akay, Semih Sami; Ozcan, Orkan; Sanli, Fusun Balik (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2022)
River basins are one of the most dynamic terrains on Earth, therefore, river morphology should be monitored continuously and its effects on the environment (i.e. natural hazards) should be mapped whenever possible. This study was carried out to quantify and visualize -flood- induced morphological changes in meander structures by UAV-based monitoring. Two-year (2018 and 2019) field surveys were conducted in the Buyuk Menderes River (BMR) Basin, Turkey. Multi-temporal orthomosaics and digital surface models (DSMs) were constructed using the Structure from Motion (SfM) technique to evaluate the change of river morphology. Diachronic spatial and volumetric changes in the meander structures were assessed by the Digital Shoreline Analysis System (DSAS) and Digital Elevation Model (DEM) of Difference (DoD) tools. This study shows the importance of mapping and monitoring river basins that have an impact on human life in many ways with evaluating and analyzing the results of extreme events such as floods promptly. (C) 2021 Karabuk University. Publishing services by Elsevier B.V.
Keywords: Natural hazard; Unmanned aerial vehicles (UAV); Multi-temporal surveys; River morphology; BANK EROSION; SFM PHOTOGRAMMETRY; RIVER; QUANTIFY; LIDAR; Engineering